2020
DOI: 10.1002/adts.202000116
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Light‐Intensity Dependence of the Short‐Circuit Current of Organic Solar Cells

Abstract: In organic solar cells, bimolecular recombination is a key factor limiting the device performance and creating the need for characterization. Light‐intensity‐dependent short‐circuit current density measurements are a frequently used tool to qualitatively analyze bimolecular recombination in a device. When applying a 0D model, bimolecular recombination is expected to reduce the otherwise linear correlation of the short‐circuit current density Jsc and the light intensity Φ to a sublinear trend. It is shown by nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 70 publications
3
54
0
1
Order By: Relevance
“…This behavior of the recombination rate coincides with what has been observed for band‐to‐band recombination in previous studies. [ 70,71 ] As a result, the recombination rate in the case of ε r = 10 5 is almost homogeneous at 10 suns. On the other hand, in the case of ε r = 3.8, the recombination rate starts to scale superlinearly with light intensity Φ in the low‐field region quickly surpassing the recombination rate at the contacts.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…This behavior of the recombination rate coincides with what has been observed for band‐to‐band recombination in previous studies. [ 70,71 ] As a result, the recombination rate in the case of ε r = 10 5 is almost homogeneous at 10 suns. On the other hand, in the case of ε r = 3.8, the recombination rate starts to scale superlinearly with light intensity Φ in the low‐field region quickly surpassing the recombination rate at the contacts.…”
Section: Resultsmentioning
confidence: 96%
“…In previous studies, it was already observed that the resulting low‐field region in proximity of the illuminated contact is more pronounced for Urbach tails with higher characteristic energy. [ 43,71 ] Hence, a thorough analysis of the photo‐induced space‐charge effect on the performance of organic solar cells with different Urbach energies under consideration of the illumination condition is required.…”
Section: Resultsmentioning
confidence: 99%
“…A linear dependence was observed when the value of S1 close to 1 indicates weak bimolecular recombination. Conversely, a value of S1 smaller than 1 suggests that bimolecular recombination of free charge carriers can limit the photocurrent devices [45]. Figs.…”
Section: Resultsmentioning
confidence: 98%
“…[70] However, this typically only affects J sc values measured at intensities around one sun and higher while there should be no non-linearities at the low light intensities relevant for indoor applications. [71,72] Figure 2c, the quantum efficiency normalized to the maximal spectral irradiance and the resulting integrated short circuit current densities are shown for an organic solar cell with PBDB-TF-T1:BTP-4F-12 (PBDB-TF-T1:Y12) as the absorber material fabricated in our group, which was first shown in ref. [73].…”
Section: Adjusting the Output Power And Visualization Of The Methodsmentioning
confidence: 99%
“…[ 70 ] However, this typically only affects J sc values measured at intensities around one sun and higher while there should be no non‐linearities at the low light intensities relevant for indoor applications. [ 71,72 ]…”
Section: Theoretical Backgroundmentioning
confidence: 99%